Treatment Effect of Mammary Duct Exploration Combined with Focal Resection on Granulomatous Lobular Mastitis - Zuo X (Dove Medical Press, 2021)
Ximeng Zuo, Xiaoguang Shi, Xiang Gao, Rui Lai, Pengzhou Liu, Ze Zhao Department of General Surgery, Dongzhimen Hospital, Beijing University of Chinese Medicine, Beijing, 100700, People’s Republic of ChinaCorrespondence: Xiaoguang ShiDepartment of General Surgery, Dongzhimen Hospital, Beijing University of Chinese Medicine, Beijing, 100700, People’s Republic of ChinaTel/Fax +86 13301119560Email shixiaoguang221@163.comObjective: This study aims to summarize the treatment of granulomatous lobular mastitis with a low recurrence rate and high satisfaction rate.Methods: In this study, the epidemiology and treatment effect was analyzed based on the general data and treatment effects. Patients treated for granulomatous lobular mastitis at the Dongzhimen Hospital, Beijing University of Chinese Medicine, and Beijing Contemporary Hospital from October 24, 2016, to May 8, 2019, were selected as subjects for the study.Results: The results revealed that the common features of granulomatous lobular mastitis were nipple retraction, history of induced abortion, nipple discharge, history of thyroid disease, history of lactation mastitis, and mental illness. The cure rate of the disease was 100%, the recurrence rate was 0.38%, and the patient satisfaction rate was 97.71%.Conclusion: The combination of mammary duct exploration and focal resection has a positive effect on the treatment of this disease and is worthy of clinical popularization.Keywords: breast duct exploration, granulomatous lobular mastitis, surgical treatment, retrospective study, prolactin